Portfolio Analysis in a Stable Paretian Market - Fama, Eugene F. (Management Science, 1965)
Recently evidence has come forth which suggests that empirical probability distributions of returns on securities conform better to stable Paretian distributions with infinite variances than to the normal distribution. Using a generalized form of a technique proposed by Sharpe [17] in a recent issue of this journal, this article develops a portfolio analysis model for a stable Paretian market. The article also shows the range of conditions under which diversification is a meaningful economic activity, even though probability distributions of returns on individual securities have infinite variances.